Malaria in Children, Prospects and Challenges - Mohammad Sadegh Rezai; Ahmad Ali Enayati; Janet Heamingway (Mazandaran University of Medical Sciences, 2013)
Malaria is still the number one killer especially among the young children and is responsible for one death per minute in the world. Overall, between 250-500 million cases of the disease occur worldwide causing more than one million deaths annually about 90% of which in children under five years of age. Although the spread of the disease is worldwide but it is seen mostly in tropical and subtropical regions of all continents and is more so in sub-Saharan Africa. Five parasite species transmitted by more than 70 potent Anopheles mosquito vectors are responsible for the occurrence of the disease and its spread. There have beenseveral approaches for malaria diagnosis, management and prevention as a whole and in children (as the most vulnerable group) in particular with various degrees of success. In this context works undertaken by international organizations such as Roll Back Malaria, Global Fund, UNICEF, as well as None for Profit international agencies and also at the national levels are promising in malaria control. However, drug and insecticide resistance, constraints in access to health care, poverty and the like are among the main challenges ahead. In this review paper the situation of malaria and its management measures with especial reference to children are discussed